Cyclodextrin-engineered bioinspired nanozyme microneedle for adaptive theranostic regulation of hyperuricemia and gout - Xu-Wei Qi; Hua-Zhou Niu; Ya-Hui Chen; Ye-Tao Zhang; Jing Li; Zu-E Hu; Jia-Xin Wang; Yi-Qi Liu; Bang-Jing Li; Sheng Zhang (Carbohydrate Polymers, 2026)

Dose-dependent modulation of the gut microbiota and metabolome by Astragalus mongholicus micropowder improves growth performance and intestinal health in weaned calves - Baoshan Feng; Hongwei Zhang; Meishu Tan; Yiran Xu; Sen Mao; Man Feng; Gui'e Jiang; Yinghao Zhou; Tingyu Liu; Yanli Chen; Yian Zhao; Hui Zhang; et al. (Animal Feed Science and Technology, 2026)

Radiocarbon Reveals Modern Carbon Exchange With Topsoil Inorganic Carbon in Drylands - Hui Wang; Jianbei Huang; Fernando T. Maestre; Guang Zhao; Nan Lu; Cong Wang; Weiliang Chen; De Shorn E. Bramble; Marion Schrumpf; Michaela A. Dippold; Yangjian Zhang; Sönke Zaehle; et al. (Global Change Biology, 2026)
Drylands store most of the global soil inorganic carbon (SIC), yet the extent to which this pool interacts with contemporary carbon (C) cycling remains poorly understood. To test whether SIC behaves primarily as an inert geological reservoir or instead bears a modern carbon imprint, we quantified SIC content and radiocarbon (∆ 14 C) at 42 dryland sites spanning broad aridity gradients across Eurasia. We also evaluated the climatic, edaphic, and biotic factors associated with variation in ∆ 14 C‐SIC. Across all sites, topsoil SIC (~0–10 cm) was strongly depleted in 14 C but consistently enriched relative to 14 C‐dead carbonates, indicating that it contains a measurable component derived from modern carbon inputs. In the Chinese drylands, ∆ 14 C‐SIC declined with increasing aridity, consistent with weaker modern carbon exchange under drier conditions and a greater contribution of inherited or 14 C‐depleted carbonate carbon. Soil pH and ∆ 14 C of soil organic carbon were the strongest predictors of ∆ 14 C‐SIC, suggesting that carbonate dissolution‐reprecipitation and the age of carbon entering soil CO 2 play key roles in determining SIC origins. At a subset of nine Chinese sites, ∆ 14 C‐SIC declined sharply with depth and approached 14 C‐dead values in subsoils, indicating little influence of modern carbon in deeper carbonate pools. The presence of mixed 14 C‐depleted and modern 14 C signatures in SIC potentially complicates the use of SIC isotopic signatures as proxies of environmental conditions. Together, our results indicate that dryland topsoil SIC commonly carries a measurable modern carbon signature that is tightly linked to contemporary carbon cycling. This coupling weakens with increasing aridity and soil depth, suggesting that environmental change in drylands may reshape one of the planet's largest carbon pools not only through changes in SIC stocks, but also through shifts in carbonate radiocarbon signatures and sources.

Antibacterial activity and mechanisms of Bacillus amyloliquefaciens HJ9 isolated from Polygonatum sibiricum against Escherichia coli - Shang-Hong Xie; Zhong-Bao Jiang; Xin-Pei Ye; Zhen-Xing Tang; Wen-Qing Xia; Shu-Qi Chen; Yu-Hang Zhou; Hui-Yang Shen; Qin Zhu; Lu-E Shi (Food Bioscience, 2026)

Production of the metabolites with antibacterial activity and its mechanism of endophyte Paenibacillus polymyxa Y4 against Staphylococcus aureus - Yan-Yu Hu; Shu-Qi Chen; Zhen-Xing Tang; Zhong-Bao Jiang; Wen-Qing Xia; Hui-Yang Shen; Qian-Yu Wang; Yue Wang; Meng-Yun Wang; Lu-E Shi (Food Bioscience, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Mesoporous CeO2 hollow-nanosphere-supported Ni catalysts for enhanced low-temperature CO2 methanation - Yutong Shen; Yike Gao; Hui Yang; Zhenyu Lu; Mengmeng Li; Cai-e Wu; Shuai Wang; Leilei Xu; Fei Gao; Mindong Chen (Journal of Environmental Chemical Engineering, 2026)

Durability analysis of using MICP to address dispersive soil issues in seasonal freezing areas - Xiaoqing Yuan; Yuhui Wu; Cencen Niu; Xiaolong Yang; Sen Lin; Zeju Wu; Qing Wang; Hui’e Chen; Xin Xu; Hua Du (Soil and Tillage Research, 2026)

Genetic dissection of low-sulfur tolerance via linkage and genome-wide association analyses in soybean [Glycine max (L.) Merr.] seedlings - Kaixin Zhang; Yanning Chen; Sujing Wang; Yu’e Zhang; Yudan Chen; Kaili Ren; Xiao Li; Guizhen Kan; Deyue Yu; Hui Wang (Theoretical and Applied Genetics, 2025)

Genome-wide Identification and Expression Analysis of the Argonaute Gene Family in Sugar Beet (Beta vulgaris L.) - Zengjuan Fu; Liang Wang; Xiaodong Li; Yuanyuan E; Yahui Liang; Bizhou Zhang; Shangmin Zhao; Hui Zhang; Wenzhe Zheng; Chen Bai; Mengyuan Sun; Ziqiang Zhang; et al. (Sugar Tech, 2025)

Development of efficient Ni-based catalysts for CO2 methanation: Unraveling the impact of support properties on catalytic performance - Xue Luo; Xueying Wen; Hui Yang; Tianmin Lu; Linshui Lian; Cai-e Wu; Zhen Cao; Shuai Wang; Leilei Xu; Mindong Chen (Journal of Environmental Chemical Engineering, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Climate, peace, and conflict—past and present: Bridging insights from historical sciences and contemporary research - Sam White; Dominik Collet; Agustí Alcoberro; Mariano Barriendos; Rudolf Brázdil; Pau Castell; Siyu Chen; Cedric de Coning; Dagomar Degroot; Lukáš Dolák; Stefan Döring; Santiago Gorostiza; et al. (Ambio, 2025)
Concern has risen that current global warming and more frequent extreme events such as droughts and floods will increase conflict around the world. This concern has spurred both social science research on contemporary climate, peace, and conflict as well as research in the historical sciences on past climate, weather, warfare, and violence. This perspectives article compares these two fields of scholarship and examines how each may benefit the other. It finds significant convergences in methods and insights across contemporary and historical research as well as persistent patterns in causal pathways between climate and conflict. Contemporary climate, peace, and conflict (CPC) research may sharpen methods and causal models for historical researchers. Historical studies, particularly those informed by contemporary research, may elucidate deep origins and long-term effects of climate-related conflicts. For policymakers and the public, history offers comprehensible ways to make sense of complex and contingent linkages and to construct cogent narratives of the past as well as storylines for the future.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Effect of Five Seed-Coating Agents on the Germination Rate and the Evaluation of Control Effect on the Damping-Off Disease of Sugar Beet - Bizhou Zhang; Chen Aidong; Mengyuan Sun; Wenzhe Zheng; Hui Zhang; Zengjuan Fu; Shangmin Zhao; Ziqiang Zhang; Liang Wang; Yuanyuan E; Huizhong Zhang; Chen Bai; et al. (Sugar Tech, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Fate of soil organic carbon in estuarine mangroves: Evidences from stable isotopes and lignin biomarkers - Guoming Qin; Zhe Lu; Shuchai Gan; Lulu Zhang; Jingfan Zhang; Jinge Zhou; Ruyi Ding; Xingyun Huang; Han Chen; Hua He; Mengxiao Yu; Hui Li; et al. (CATENA, 2024)

Mycorrhizal association controls soil carbon-degrading enzyme activities and soil carbon dynamics under nitrogen addition: A systematic review - Yuanliu Hu; Ji Chen; Jørgen E. Olesen; Kees Jan van Groenigen; Dafeng Hui; Xinhua He; Guoyin Chen; Qi Deng (Science of The Total Environment, 2024)

Salt Stress Induces Complicated miRNA Responses of Sugar Beet (Beta vulgaris L.) - Ziqiang Zhang; Zengjuan Fu; Wenjin Chen; Liang Wang; Shangmin Zhao; E Yuanyuan; Hui Zhang; Bizhou Zhang; Mengyuan Sun; Wenzhe Zheng; Jing Dong; Zhiqi Zhang; et al. (Sugar Tech, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Numerical simulation of the cloud seeding operation of a convective rainfall event occurred in Beijing - Shaofeng Hua; Baojun Chen; Hui He; Yichen Chen; Xiang’e Liu; Jing Yang (Atmospheric Research, 2024)

Effects of hypertension and use of antihypertensive drugs in pregnancy on the risks of childhood cancers in Taiwan - Helen T. Orimoloye; Ya-Hui Hu; Noah Federman; Beate Ritz; Onyebuchi A. Arah; Chung-Yi Li; Pei-Chen Lee; Julia E. Heck (Cancer Causes & Control, 2024)

Facilely preparing highly dispersed Ni-based CO2 methanation catalysts via employing the amino-functionalized KCC-1 support - Siyuan Yin; Chunying Xu; Hui Yang; Cai-e Wu; Mei Wu; Jingxin Xu; Hao Zhu; Jian Qiu; Leilei Xu; Mindong Chen (Fuel, 2024)

Stress ratio sensitivity—a novel parameter for evaluating the shearing-based structural characteristic of loess - Meng Yao; Hui-e Chen; Hui Li; Qing wang; Yan Han; Qingbo Yu; Yibo Liu (Bulletin of Engineering Geology and the Environment, 2024)

Permeability of High Clay Content Dredger Fill Treated by Step Vacuum Preloading: Pore Distribution Analysis - Wenchong Shan; Xiaoqing Yuan; Hui-e Chen; Xiaolin Li; Jinfeng Li (Journal of Marine Science and Engineering, 2023)
In this study, the step vacuum preloading method was used to reinforce high clay content dredger fill in the laboratory. The pore structures and permeability characteristics of dredger fill under different vacuum pressures were tested. The correlation between the pore structure parameters and permeability coefficient was analyzed using the grey T’s correlation analysis method. The research results indicate that the pore ratio, large pore (the diameter with a range of 4–40 μm) content, and permeability coefficient of dredger fill decreased with the increase in vacuum pressures, but the decrease rates of the pore ratio were different at various sampling locations. The contents of micropores (the diameter with a range of

Highly fractionated Hg isotope evidence for dynamic euxinia in shallow waters of the Mesoproterozoic ocean - Yaowen Wu; Hui Tian; Runsheng Yin; Di Chen; Stephen E. Grasby; Jun Shen; Tengfei Li; Sui Ji; Ping'an Peng (Earth and Planetary Science Letters, 2023)

An Efficient Protocol for Agrobacterium-Mediated Transformation and Regeneration of Sugar Beet (Beta vulgaris L.) based on Blade–Petiole Transition Zone Explants - Ziqiang Zhang; Huizhong Zhang; Liang Wang; Bizhou Zhang; Zengjuan Fu; Shangmin Zhao; E Yuanyuan; Wenzhe Zheng; Hui Zhang; Pingan Han; Wenjin Chen; Yue Chang; et al. (Sugar Tech, 2023)

Isolation and Identification of Aroma-producing Yeast from Mackerel Fermentation Broth and Its Fermentation Characteristics - Yu Wu; Xiao’e Chen; Xubo Fang; Lili Ji; Fang Tian; Hui Yu; Yan Chen (Journal of Aquatic Food Product Technology, 2021)

Elevated L-lactate Promotes Major Cellular Pathologies Associated with Neurodegenerative Diseases - Andrew D. Chapp; Jessica E. Behnke; Kyle M. Driscoll; Taija Hahka; Zoe LaLonde; Zhiying Shan; Qing-Hui Chen (Neuroscience Bulletin, 2021)

Mechanism of pore water seepage in soil reinforced by step vacuum preloading - Wenchong Shan; Hui-e Chen; Xiaoqing Yuan; Wenliang Ma; Hui Li (Bulletin of Engineering Geology and the Environment, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

Modeling Arctic Boundary Layer Cloud Streets at Grey-zone Resolutions - Hui-Wen Lai; Fuqing Zhang; Eugene E. Clothiaux; David R. Stauffer; Brian J. Gaudet; Johannes Verlinde; Deliang Chen (Advances in Atmospheric Sciences, 2020)

Seasonal changes in the chemical composition and reactivity of dissolved organic matter at the land-ocean interface of a subtropical river - Liyang Yang; Qiong Cheng; Wan-E Zhuang; Hui Wang; Wei Chen (Environmental Science and Pollution Research, 2019)

Anxiolytic potency of iridoid fraction extracted from Valeriana jatamansi Jones and its mechanism: a preliminary study - Xue-Mei Zhang; Jia-Li Zhu; Yong Sun; Yao-Lan Dai; Xiu Chen; Jia-Hong Cao; Ruo-Cong Yang; Chang Chen; Chao-Ying Ma; Tian-E Zhang; Yun-Hui Chen; Zhi-Yong Yan (Natural Product Research, 2018)

Indoor simulation test of step vacuum preloading for high-clay content dredger fill - Xiao-qing Yuan; Qing Wang; Wen-xi Lu; Wen Zhang; Hui-e Chen; Ying Zhang (Marine Georesources & Geotechnology, 2018)

Calculation Method and Distribution Characteristics of Fracture Hydraulic Aperture from Field Experiments in Fractured Granite Area - Yang-Bing Cao; Xia-Ting Feng; E-Chuan Yan; Gang Chen; Fei-fei Lü; Hui-bin Ji; Kuang-Yin Song (Rock Mechanics and Rock Engineering, 2016)

FBXW7-Induced MTOR Degradation Forces Autophagy to Counteract Persistent Prion Infection - Yin Xu; Chan Tian; Jing Sun; Jin Zhang; Ke Ren; Xue-Yu Fan; Ke Wang; Hui Wang; Yu-E Yan; Cao Chen; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2016)

Next-generation sequencing-based molecular diagnosis of 82 retinitis pigmentosa probands from Northern Ireland - Li Zhao; Feng Wang; Hui Wang; Yumei Li; Sharon Alexander; Keqing Wang; Colin E. Willoughby; Jacques E. Zaneveld; Lichun Jiang; Zachry T. Soens; Philip Earle; David Simpson; et al. (Human Genetics, 2015)

New species and new records of Rhytismataceae from Japan - Zhi-Jie Li; Ning Cao; Hui-Fen Chen; J. E. Taylor; Cheng-Lin Hou (Mycological Progress, 2014)

Overexpression of p62/SQSTM1 promotes the degradations of abnormally accumulated PrP mutants in cytoplasm and relieves the associated cytotoxicities via autophagy–lysosome-dependent way - Yin Xu; Jin Zhang; Chan Tian; Ke Ren; Yu-E Yan; Ke Wang; Hui Wang; Cao Chen; Jing Wang; Qi Shi; Xiao-Ping Dong (Medical Microbiology and Immunology, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Perspectives on Disconnects Between Scientific Information and Management Decisions on Post-fire Recovery in Western US - Xiaoli Chen; Nathan Emery; Elizabeth S. Garcia; Erin J. Hanan; Heather E. Hodges; Tyronne Martin; Matthew A. Meyers; Lindsey E. Peavey; Hui Peng; Jaime Sainz Santamaria; Kellie A. Uyeda; Sarah E. Anderson; et al. (Environmental Management, 2013)

Combining genetical genomics and bulked segregant analysis-based differential expression: an approach to gene localization - Xinwei Chen; Peter E. Hedley; Jenny Morris; Hui Liu; Rients E. Niks; Robbie Waugh (Theoretical and Applied Genetics, 2011)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

AICAR inhibits the Na+/H+ exchanger in rat hearts—possible contribution to cardioprotection - Terence R. Moopanar; Xiao-Hui Xiao; Lele Jiang; Zhi-Ping Chen; Bruce E. Kemp; David G. Allen (Pflügers Archiv - European Journal of Physiology, 2006)

Ripening-related occurrence of phosphoenolpyruvate carboxykinase in tomato fruit - Ahmad R. Bahrami; Zhu-Hui Chen; Robert P. Walker; Richard C. Leegood; Julie E. Gray (Plant Molecular Biology, 2001)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)